1970
DOI: 10.33422/ejbs.v2i3.151
|View full text |Cite
|
Sign up to set email alerts
|

Urine Diversion Dry Toilet: A Narrative Review on Gaps and Problems and its Transformation

Abstract: This review paper highlights the gaps and problems on source separation of human excreta; implementing and adopting human urine as nutrients for agriculture. The objective of the paper is to appraise the historical context behind the promotion of Urine Diversion Dry Toilet/Eco-san toilet and its relevance in rural Nepalese context. Moreover, it highlights the experiences regarding agricultural perspectives and livelihood by applying human urine as a fertilizer. Furthermore, it helps to understand and analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…These systems are more advantageous in areas of water scarcity as they preserve groundwater from contamination by pathogens and microorganisms. In addition, human excreta contain high levels of nitrogen, phosphorus and potassium needed for plant growth (Prasad Devkota et al 2019). One study showed that in 2009, the total available phosphorus in feces was about 1.68 million tons, which could meet 22% of the total global demand for phosphorus (Mihelcic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These systems are more advantageous in areas of water scarcity as they preserve groundwater from contamination by pathogens and microorganisms. In addition, human excreta contain high levels of nitrogen, phosphorus and potassium needed for plant growth (Prasad Devkota et al 2019). One study showed that in 2009, the total available phosphorus in feces was about 1.68 million tons, which could meet 22% of the total global demand for phosphorus (Mihelcic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nepal is one of the countries that has developed technology to manufacture fertilizer from human urine through the Urine Diversion Dry Toilet. However, suctioning and harvesting fertilizer are done manually (Devkota et al, 2019). A pilot plant for processing urine-based fertilizers has been built in Durban, South Africa, involving household toilets as a producer of materials for fertilizer production.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, only urine can be deposited through urinal and used as fertilizer by dilution of certain amount of water. For this, urine need to be collected in the chamber stored it for 15-20 days to destroy micro-organisms (Devkota, Pandey, & Maharjan, 2019). Eco-san is beneficial because the system is safer hygienically, due to the access to improved sanitation and the recycling of valuable nutrients as fertilizer (Werner, Panesar, Rüd, & Olt, 2009).…”
Section: Introductionmentioning
confidence: 99%